LCZ696: a new paradigm for the treatment of heart failure?. (February 2015) - Minguet, Joan; Sutton, Gemma; Ferrero, Carmen; Gomez, Timothy; Bramlage, Peter
<x xml:space="preserve">Abstract</x> Introduction: Heart failure (HF) represents a significant healthcare issue because of its ever-increasing prevalence, poor prognosis and complex pathophysiology. Currently, blockade of the renin–angiotensin–aldosterone system (RAAS) is the cornerstone of treatment; however, the combination of RAAS blockade with inhibition of neprilysin (NEP), an enzyme that degrades natriuretic peptides, has recently emerged as a potentially superior treatment strategy. Areas covered: Following the results of the recent Phase III Prospective Comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure clinical trial in patients with chronic HF with reduced ejection fraction (HF-REF), this review focuses on <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=LCZ696&logicalOpe1=OR&field2=articletitle&text2=LCZ696&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">LCZ696, a first-in-class angiotensin receptor NEP inhibitor. This drug consists of a supramolecular complex containing the angiotensin receptor inhibitor valsartan in combination with the NEP inhibitor prodrug, AHU377. Following oral administration, the LCZ696 complex dissociates and the NEP inhibitor component is metabolized to the active form (LBQ657). Aspects of the trial that might be relevant to clinical practice are also discussed. Expert opinion: Speculation that LCZ696 will pass the scrutiny of regulatory agencies for HF-REF appears to be justified, and it is likely to become a core therapeutic component in the near future. Replication of the eligibility criteria and titration protocol used in the PARADIGM-HF trial would be valuable in clinical practice and may minimize the risk of adverse events. Although long-term data remain to be generated, the promising results regarding hypertension are likely to expedite acceptance of the drug for HF-REF.